Concealed pregnancy as an act of care? A qualitative analysis of motivations for concealing and non-disclosure of early pregnancy in The Gambia - Sabine Parrish; Senthil K. Vasan; Fredrik Karpe; Polly Hardy-Johnson; Ousman Jarjou; Mustapha Bittaye; Andrew M. Prentice; Stanley Ulijaszek; Modou Jobe (BMC, 2023)
Abstract Background A barrier to achieving first trimester antenatal care (ANC) attendance in many countries has been the widespread cultural practice of not discussing pregnancies in the early stages. Motivations for concealing pregnancy bear further study, as the interventions necessary to encourage early ANC attendance may be more complicated than targeting infrastructural barriers to ANC attendance such as transportation, time, and cost. Methods Five focus groups with a total of 30 married, pregnant women were conducted to assess the feasibility of conducting a randomised controlled trial to evaluate the effectiveness of early initiation of physical activity and/or yoghurt consumption in reducing Gestational Diabetes Mellitus in pregnant women in The Gambia. Focus group transcripts were coded through a thematic analysis approach, assessing themes as they arose in relation to failure to attend early ANC. Results Two reasons for the concealment of pregnancies in the first trimester or ahead of a pregnancy's obvious visibility to others were given by focus group participants. These were 'pregnancy outside of marriage' and 'evil spirits and miscarriage.' Concealment on both grounds was motivated through specific worries and fears. In the case of a pregnancy outside of marriage, this was worry over social stigma and shame. Evil spirits were widely considered to be a cause of early miscarriage, and as such, women may choose to conceal their pregnancies in the early stages as a form of protection. Conclusion Women's lived experiences of evil spirits have been under-explored in qualitative health research as they relate specifically to women's access to early antenatal care. Better understanding of how such sprits are experienced and why some women perceive themselves as vulnerable to related spiritual attacks may help healthcare workers or community health workers to identify in a timely manner the women most likely to fear such situations and spirits and subsequently conceal their pregnancies.